(untitled) (Architecture Image Studies, 2023)
As a part of this year’s call for submissions to the journal, we invite contributions that reflect on the role of Architecture Images Studies (AIS) on the current “Liminal” times. Questions of interest include, but are not limited to, the following: Were and how Architecture Images Studies relate with a polarized world? Which/whose are the limits of Architecture Images Studies concepts and how this discussion contribute to the present global challenges? What methodological experiments are you undertaking and what methods are being developed? Which novel theoretical insights can we draw upon to bring the Architecture Images Studies (AIS) forward? In addition to this specific themed call for submissions we also welcome contributions that deal in a more general way with issues pertaining to AIS. We remind that AIS Journal is focused on the image production realms that are connected with Architecture and Design, among others architectural and design photography, 2D and 3D drawing technologies (CAD) project and inspirational illustration.